The influence of neighborhood structure on the determinants of parenting for mothers of urban and suburban Manila - Sabido, Brian Alan L.
In response to urban decay and the need to counterbalance suburban development in consideration to its consequent adverse environmental effects, urban design literature promotes urban development where lifestyles of greater efficiencies in accessing goods/services/activities to meet needs can be achieved. Understanding the contrast between the neighborhood structures of the urban and suburban environment is crucial in this aspect. In this light, the study, in the context of metropolitan region of Manila, examined the influence of neighborhood structure on parenting by examining how it affects a mother's ease of accessing goods/services/activities where it is argued that urban environments are more beneficial to families in raising children. The study involved a comparison on findings on identified measures associated to accessing lower-order and higher-order goods/services/activities between mothers of an urban group and a suburban group. Data was gathered through surveys and interviews. Findings run counter to the argument revealing that the suburban environment is more beneficial to families where the suburban group reported lower travel time, better proximities to lower-order goods/services/activities, lower parental stress levels, higher frequencies in leisure time with children, and more positive child-parent relationships. Findings reveal considerable differences between the urban and suburban group in the travel time in the trips between the house and the school. Findings suggest that, in the context of Manila's neighborhood structure influencing mother's travel behavior where private car use is the predominant mode of transportation, family housing densities in relation to existing schools' and concentration of schools' capacities are most influential.